Pengaruh Penambahan Minyak Kelapa Murni terhadap Sifat Perekat Berbahan Dasar Tepung Tapioka - Vincent; Pancasakti, Bima Prasetya; Budhijanto (Talenta Publisher (Universitas Sumatera Utara), 2022)
Wood adhesive has significant contribution in the development of furniture industries. Currently, the most widely used type of adhesives is synthetic adhesive which is carcinogenic to humans. This research aimed to develop cassava starch-based bioadhesive. The additive added to the adhesive was virgin coconut oil (VCO) which had antibacterial and antifungal properties. The research method used is quantitative approach where adhesives were made and the properties were analyzed. The steps of making the adhesives included hydrolysis reaction, oxidation, and VCO addition. The reaction was carried out at 70 â„ƒ and atmospheric pressure for 90 minutes. The amount of VCO added were varied to 0%, 10%, 15%, 20%, 25%, and 30% of the weight of cassava starch. The properties measured were viscosity, solid content, shelf life, shear strength, and the molecular structure of the adhesives. The results showed that the addition of VCO improved the shelf life of the adhesive but weakened the shear strength of the adhesive. The amount of VCO that should be added to improve the adhesive quality is 10% of the weight of cassava starch.